Alfred Jarry en Catalogne - Anna Corral Fullà (Mélanges de la Casa de Velázquez, 2017)
The reception of Alfred Jarry’s celebrated play, Ubu Roi, in Catalonia can be traced indirectly through the plastic arts. Picasso and Miró both began on their «Ubu(s)» at the beginning of the 20th century, many years before the play was first staged in Barcelona in 1964 or the first Spanish translation, by José Corrales Egea, published by Aymà, S.A., a few years later (Barcelona, 1967). This study proposes to trace this path, which began in painting and emerged later on the Catalan stage, with manifold performances and adaptations which have left their mark on Catalan theatre.